Analysis of the Use of Village Fund Allocation in Fostering Community Creativity in Angkue Village, Kajuara District - Adismayana Adismayana; Hasdinawati Hasdinawati; Mursak Mursak; Abd. Rahman (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2021)
The Village Fund Allocation is a fund whose budget is from the state revenue and expenditure budget allocated for villages which are transferred through the district or city-regional revenue and expenditure budget and are used to finance government administration, development implementation, community development, and community empowerment. This type of research is qualitative. This study uses data collection techniques, namely observation, interviews, and documentation. The informants of this study were the Head of Angkue Village, Kajuara District, Secretary of Angkue Village, Kajuara District, BPD Angkue Village, Angkue Village Community who knew a lot about research. The data analysis techniques used are data reduction, data presentation, and conclusions. Next, the purpose of this study was to determine the use of village fund allocations in fostering community creativity in Angkue Village. The results show that the use of village fund allocations in fostering community creativity in Angkue Village, Kajuara District has not been realized optimally. Likewise, job training and skills for rural communities according to village conditions have not been realized, this is evidenced by the village government which has not budgeted for job training and skills for rural communities according to village conditions, so the form of activity does not exist.